Rapid ventricular overdrive pacing and other advanced flow-control techniques for the endovascular embolization of vein of galen malformations - Baranoski, Jacob F.; Catapano, Joshua S.; Albuquerque, Felipe C.; Abruzzo, Todd A. (Frontiers in Pediatrics, 2023)
Endovascular embolization is the primary strategy in the management for vein of Galen malformations (VOGM). However, despite significant advances in endovascular embolization technologies and techniques, VOGMs remain very technically challenging lesions largely due to the high-flow arteriovenous shunts present in these malformations. A variety of advanced flow-control techniques can be implemented to mitigate the risk of venous escape and increase the safety and efficacy of endovascular treatment. These techniques include regionally targeted strategies (transvenous embolization and balloon-assisted transarterial embolization) and global flow-control methods (pharmacologic cardiac arrest and rapid ventricular overdrive pacing). Each of these strategies are associated with unique advantages and disadvantages, highlighting the importance of a patient-specific approach when treating these challenging lesions.